A genetically encoded fluorescent biosensor for sensitive detection of cellular c-di-GMP levels in Escherichia coli - Li, He; Quan, Shu; He, Wei (Frontiers in Chemistry, 2025)
Cyclic di-guanosine monophosphate (c-di-GMP) acts as a second messenger regulating bacterial behaviors including cell cycling, biofilm formation, adhesion, and virulence. Monitoring c-di-GMP levels is crucial for understanding these processes and designing inhibitors to combat biofilm-related antibiotic resistance. Here, we developed a genetically encoded biosensor, cdiGEBS, based on the transcriptional activity of the c-di-GMP-responsive transcription factor MrkH. Notably, cdiGEBS can detect both low and high cellular c-di-GMP levels, with a high fluorescence dynamic change of 23-fold. Moreover, it can detect subtle changes in c-di-GMP concentrations due to variations in the expression of c-di-GMP synthesis or degradation enzymes and can distinguish different synthesis activities among WspR mutants. These capabilities allow us to apply cdiGEBS for identifying new diguanylate cyclases and evaluating chemicals that modulate c-di-GMP levels, highlighting its potential as a high-throughput tool for screening inhibitors of c-di-GMP synthesis enzymes. Overall, cdiGEBS enhances the study of c-di-GMP-regulated functions and holds the potential for screening antimicrobials targeting c-di-GMP or its synthesis enzymes.